1935
DOI: 10.1007/bf01764161
|View full text |Cite
|
Sign up to set email alerts
|

Über die Abhängigkeit der Zeiterregbarkeit des motorischen Nerven vom Dehnungszustand seines Muskels

Abstract: L. und M. Lapicque 1 haben die interessante Beobachtung beschrieben, dab sich die Chronaxie eines noeh mit dem Rfiekenmark verbundenen motorischen 1Nerven verkfirzt, wenn der yon dem betreffenden Nerven versorgte Muskel passiv gedehnt wird.Es lag nahe zu untersuchen, ob in diesem, wie in manchen anderen Fs die Umstimmung des Nerven auf dem Wege fiber das vegetative System erfolgt. Diese Analyse erwies sieh, wenigstens am Frosch, als nieht durchffihrbar ; abet bei der grunds/~tzlichen Wichtigkeit der Lapicquese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1937
1937
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experiments show that stretching causes changes in nerve function. As early as 1935 (124) showed that the chronaxie of motor nerve stimulation changes with stretching. The effect of stretching on reflexes has been studied extensively (125).…”
Section: Stretching Of Nervesmentioning
confidence: 99%
“…Experiments show that stretching causes changes in nerve function. As early as 1935 (124) showed that the chronaxie of motor nerve stimulation changes with stretching. The effect of stretching on reflexes has been studied extensively (125).…”
Section: Stretching Of Nervesmentioning
confidence: 99%